2015
DOI: 10.1002/hbm.22874
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated corpus callosum development in prematurity predicts improved outcome

Abstract: This study is the first to demonstrate an accelerated trajectory of CC white matter diffusion following VP birth, associated with improved neurodevelopmental functioning. Findings suggest there is a window of opportunity for neurorestorative intervention to improve outcomes. Hum Brain Mapp 36:3733-3748, 2015. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 70 publications
8
26
0
Order By: Relevance
“…Studies also show abnormal microstructural organization in a number of white matter pathways in the preterm brain, including the internal capsule, external capsule, inferior fronto-occipital fasciculus, uncinate fasciculus, superior longitudinal fasciculus, inferior longitudinal fasciculus, centrum semiovale (Nagy et al , 2003, Skranes et al , 2007, Constable et al , 2008, Mullen et al , 2011, Jo et al , 2012, Lee et al , 2013, Groeschel et al , 2014), and corpus callosum (Thompson et al , 2014), which has previously been reported for the current cohort. dMRI studies exploring structure-function associations in preterm cohorts have found that alterations in white matter microstructure are related to motor deficits (Skranes et al , 2007, Counsell et al , 2008, Rose et al , 2009, Thompson et al , 2012, van Kooij et al , 2012, Northam et al , 2012 ), neurosensory impairments (Bassi et al , 2008, Berman et al , 2009, Reiman et al , 2009, Glass et al , 2010, Groppo et al , 2014), and behavioral dysfunction (Nagy et al , 2003, Skranes et al , 2007, Rogers et al , 2012).…”
Section: 1 Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…Studies also show abnormal microstructural organization in a number of white matter pathways in the preterm brain, including the internal capsule, external capsule, inferior fronto-occipital fasciculus, uncinate fasciculus, superior longitudinal fasciculus, inferior longitudinal fasciculus, centrum semiovale (Nagy et al , 2003, Skranes et al , 2007, Constable et al , 2008, Mullen et al , 2011, Jo et al , 2012, Lee et al , 2013, Groeschel et al , 2014), and corpus callosum (Thompson et al , 2014), which has previously been reported for the current cohort. dMRI studies exploring structure-function associations in preterm cohorts have found that alterations in white matter microstructure are related to motor deficits (Skranes et al , 2007, Counsell et al , 2008, Rose et al , 2009, Thompson et al , 2012, van Kooij et al , 2012, Northam et al , 2012 ), neurosensory impairments (Bassi et al , 2008, Berman et al , 2009, Reiman et al , 2009, Glass et al , 2010, Groppo et al , 2014), and behavioral dysfunction (Nagy et al , 2003, Skranes et al , 2007, Rogers et al , 2012).…”
Section: 1 Introductionsupporting
confidence: 85%
“…Finally, to identify the corpus callosum a single ROI was traced on the mid-sagittal slice of the structural T1 scan and overlaid on the diffusion image as previously reported (Thompson et al , 2014) (Fig. 4).…”
Section: 2 Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of WM structure have tended to focus on individual WM regions using methods such as tractography or regions of interest. These previous studies have shown that VP children have altered microstructure in specific tracts such as the corpus callosum, corticospinal tracts or optic radiations, which often correlate with neurodevelopmental delays (Pannek et al, 2014b; Thompson et al, 2015). However, in contrast to previous regional studies, the graph theory method used in the current study enabled us to provide novel evidence that the complexity of the whole brain connectome is altered in VP children.…”
Section: Discussionmentioning
confidence: 97%
“…Recent reports in school-age children revealed fractional anisotropy in the corpus callosum and fractional anisotropy-weighted global efficiency of the entire brain network to be related to measures of intelligence and mathematical skills in both healthy children born at term and preterm. 8,19,20 The latter connectivity measure reflects how well the white matter framework is able to support global information transfer across different sites of the brain. These studies had a cross-sectional design, measuring both DWI and cognitive measures in childhood.…”
Section: Discussionmentioning
confidence: 99%